DRIVER FATIGUE ACCIDENT PREVENTION USING EYE BLINK SENSOR - AZIZAN, SITI ROSMA (Universiti Teknologi Petronas, 2013)
This paper proposes a way to detect the level of fatigue among drivers through detection of eye blinks. Fatigue or tiredness is one of the main factors that cause road accidents. Drivers who are not fit to drive a car due to fatigue may lose focus and make poor judgments while driving and consequently cause road accidents. By detecting parameters such as the duration of eye closure and reopening during blinks, drivers will realize whether they are in a fatigue condition or not. This project is done by performing data collection through previous researches. The algorithms will be modified and implemented to validate the system. A camera will be used to locate the face and narrow the scope further down to the eye region. After extracting the eye region, the algorithm will be used to detect the duration of each eye blinks in order to detect fatigue.